Syair-Syair Tasawuf Hamzah Fansuri dan Pengaruhnya - W.M, Abdul Hadi (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2007)
The treasures literary of Nusantara mystic (sufi), that especially written in Malay (Melayu) language in Indonesia are not studied anymore, recently. This is too ironical situation because of these works are relevant with strong public's animo to study Islamic mysticism (tasawuf). One of the most famous of Nusantara mystic (sufi) is Hamzah Fansuri who lived at 16-17 century.